The effect of different loads on semi-tethered swimming and its relationship with dry-land performance variables - Cuenca-Fernandez, F.; Gay, A.; Ruiz-Navarro, J. J.; Arellano, R. (International Journal of Performance Analysis in Sport, 2020)
Semi-tethered loaded swimming (denoted STLS) has been used widely to develop or test swimmers skills, although its transference to increase performance seems overestimated. In addition, its relationship with dry-land tests remains obscured by imprecise reports. Sixteen competitive male swimmers (age: 18.31 ± 1.42) participated in a two-fold purpose study: Firstly, swimming performance was assessed at different STLS intensities on an adapted Smith Machine. A repeated measures 1-way ANOVA was conducted to find differences between the variables collected through a linear encoder at 15%, 30%, 45% and 60% of the maximal load (ML). Secondly, the relationships between the swimming velocities and the different sorts of variables obtained on a dry-land arm-stroke strength test were studied by Pearson`s correlation coefficient (r). The results showed that less velocity, acceleration and impulse were delivered at high loads (p < 0.001). It increased the velocity fluctuation, affecting the swimming patterns adversely. On the other hand, the correlations between velocity-based dry-land variables and swimming velocities (r = 0.71) seem to be more suitable to predict swimming performance, rather than strength-based variables (r = 0.49). In conclusion, coaches should reconsider using STLS, as little or no benefit may be obtained in performance.